Variasi Morfologi dan Jenis Inang dari Cyclodontostomum purvisi (Adam, 1933) (Nematoda: Strongyloidea) di Indonesia - Purwaningsih, Endang (Universitas Atma Jaya Yogyakarta, 2003)
Cyclodontostomum purvisi (Adam, 1933) is a nematode infects small mammals belongs to family Muridae (Rattus spp and Maxomys spp) in Kalimantan, Sulawesi and Java. There are some morphological variation on those nematode such as the number of corona radiata elements and head orientation (the angle between cephalic collar and sagital body axis). The angle is stronger in the specimens from Kalimantan and decreasing in the specimens in Sulawesi and Java. R. exulans from Kalimantan and R. tanezumi from Sulawesi are the new host record for C. purvisi in Indonesia.